The Association of the Pulmonary Artery Pulsatility Index and Right Ventricular Function after Cardiac Surgery - Johnny Wei; Abigail Kee; Rachel Dukes; Jack Franke; Vincent Leonardo; Brigid C. Flynn (Critical Care Research and Practice)
Background. The pulmonary artery pulsatility index (PAPi) has been shown to correlate with right ventricular (RV) failure in patients with cardiac disease. However, the association of PAPi with right ventricular function following cardiac surgery is not yet established. Methods. PAPi and other hemodynamic variables were obtained postoperatively for 959 adult patients undergoing cardiac surgery. The association of post-bypass right ventricular function and other clinical factors to PAPi was evaluated using linear regression. A propensity-score matched cohort for PAPi ≥ 2.00 was used to assess the association of PAPi with postoperative outcomes. Results. 156 patients (16.3%) had post-bypass right ventricular dysfunction defined by visualization on transesophageal echocardiography. There was no difference in postoperative PAPi based on right ventricular function (2.12 vs. 2.00, p=0.21). In our matched cohort (n = 636), PAPi < 2.00 was associated with increased incidence of acute kidney injury (23.0% vs 13.2%, p<0.01) and ventilator time (6.0 hours vs 5.6 hours, p=0.04) but not with 30-day mortality or intensive care unit length of stay. Conclusion. In a general cohort of patients undergoing cardiac surgery, postoperative PAPi was not associated with postcardiopulmonary bypass right ventricular dysfunction. A postoperative PAPi < 2 may be associated with acute kidney injury.